Artificial Intelligence for Healthcare Systems of Developing World: Opportunities and Risks - Dissanayake, Maheshi (Advances in Technology, 2022)
Artificial Intelligence (AI) is now everywhere. It refers to systems that demonstrate intelligent behavior, such as the ability to analyze their environment to take action that is typically displayed by humans and animals. AI-embedded devices possess the ability to learn through example scenarios and past data presented to the system. The word AI was first introduced to the research community in 1956 at a conference at Dartmouth College in the United States [1]. With time, the AI industry expanded from data to information, then to knowledge, and ultimately to intelligence. Due to the depth and breadth of learning capacity associated with AI technologies, today it has become one of the hottest research areas, finding applications in but not limited to computer vision, marketing, industrial automation, big data, and the Internet of things (IOT).